VD_FINDINFO Décision / 2022 / 129 vom 31. Dezember 2021 - VD Tribunal cantonal (2021)
MOTIVATION DE LA DEMANDE, NON-LIEU, IN DUBIO PRO DURIORE, DIFFAMATION, CALOMNIE | 173 ch. 1 CP, 174 ch. 1 CP, 31 CP, 310 CPP (CH), 385 al. 1 CPP (CH)